INVENTARISASI Amorphophallus spp. DI TAMAN BIODIVERSITAS HUTAN HUJAN TROPIS LEMBAH BUKIT MANJAI - Safitri, Yulina; Nurtamara, Luthfiana; Amintarti, Sri (Biospecies, 2026)
South Kalimantan is known for its rich biodiversity, particularly within the Tropical Rainforest Biodiversity Park of Lembah Bukit Manjai, which serves as a habitat for various tropical forest plant species. Among these is the genus Amorphophallus, notable for its ecological, economic, and conservation value. These plants typically grow in shaded and humid forest floors. This study aimed to identify and describe Amorphophallus species present in the study area. A descriptive-exploratory method was applied using purposive sampling. The study recorded three species: Amorphophallus muelleri, A. paeoniifolius, and A. borneensis. These species were found thriving under low to moderate light intensity, high soil moisture, and neutral pH. Key morphological traits such as habit, leaves, stems, and roots were documented for each species. The findings indicate that the ecological conditions of the study area strongly support the growth of Amorphophallus spp., and that these plants hold potential as local biodiversity-based learning resources.